Eglı’s Mülkiye: Ankara’s Modern Heritage and Its Transformation - Yabacı, Azize Elif; Dinler, Mesut (ICONARCH International Congress of Architecture and Planning, 2017)
Modern architecture, especially in the non-European territories, has been utilized to represent a breaking point from the past. This pattern has repeated also in Turkey to create a secular modern nation (Turkey Republic) out of a centuries-old Islamic dynasty (the Ottoman Empire). Foreign architects have been invited by the young Republic not only to design the cities and buildings but also to teach in academia. Austrian-Swiss architect Ernst Egli (1893-1974) has been one of the prominent names of European architects/planners whose works constitute Ankara’s modern heritage. His 1936 project for the School of the Political Sciences represents the modern face of Turkish Republic. This research analyzes the place that this campus building holds within the modern architectural heritage of the Republican era, and it assesses the place of this heritage in the memory of people.